Analisis Faktor Ukuran Perusahaan, Struktur Kepemilikan, dan Profitabilitas terhadap Ketepatan Waktu Pelaporan Keuangan - Ferdianti, Desi; Riswan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Those studies goals are designed to observe the factor evaluation of company size, ownership structure, and profitability on the time of financial reporting. Thisstudies is absolutely primarily based on financial statements of banking corporations listed to Indonesia stock exchange. A focused sampling method became used within the sampling of this examine. The records evaluation technique used on this examine is logistic regression evaluation. The statistics used on this examine had been received from secondary statistics in the form of annual accounts of organizations listed in Indonesia stock trading (IDX 2018-2020). The consequences of this examine imply that ownership structure has a positive and insignificant effect on financial reporting timeliness, even if company size and profitability have a positive and significant effect on financial reporting timeliness. Keywords: Size1; Ownership 2; Profitability3 ; On Timeliness 4